Peran “Katuas Adat” (Tua Adat) dalam Menyelesaikan Sengketa Tanah di Desa Motaulun Kecamatan Malaka Barat Kabupaten Malaka (Lembaga Pengembangan Kinerja Dosen, 2025)
This thesis is titled “The Role of the ‘Katuas Adat’ (Traditional Elders) in Resolving Social Conflicts in Motaulun Village (A Study on Dispute Resolution in Motaulun Village, West Malaka Sub-District, Malaka Regency).” The research problem examined is: How is the role of the ‘Katuas Adat’ (Traditional Elders) in resolving disputes in Motaulun Village, West Malaka Sub-District, Malaka Regency? The objective of this study is to describe and analyze the extent to which the ‘Katuas Adat’ (Traditional Elders) play a role in resolving conflicts occurring in Motaulun Village. This research uses the theory of role by Horoepoetri, Arimbi, and Santoso, which includes five dimensions: the dispute resolution dimension, communication dimension, policy dimension, strategy dimension, and therapy dimension. The study employs a qualitative approach with a descriptive research type. Data collection techniques include observation and interviews. The subjects in this research consist of the ‘Katuas Adat’ (Traditional Elders), the village head, community leaders, women leaders, Bhabinkamtibmas (community police), and residents of Motaulun Village.The methods used are interviews and documentation. Based on the results of this research, it can be concluded that the ‘Katuas Adat’ (Traditional Elders) play several roles in conflict resolution. First, in the dispute resolution dimension.